Avaliação hemostática e molecular em mulheres com câncer de mama receptor hormonal negativo - Anna Paula de Borba Batschauer (2009)
The breast cancer is the most common cause of death in women by malignant disease. The mechanisms related to recurrence are unclear, especially the hemostatic alterations that occur during the development of the disease and seem to be related to its aggressiveness. The study had as aim to assess in women with hormone negative receptor breast cancer, in a 24 months period, possible hemostatic and molecular alterations in order to associate them with prognosis markers already established in three different occasions: immediately after the breast cancer diagnosis, at the end of the chemotherapy and two years after the disease diagnosis. Thirty three patients with hormone negative receptor breast cancer and a control group with sixty three women, with no history of cancer have been studied. As hemostatic markers, plasma D dimmer and tissue factor levels were measured. Mutations/polymorphisms in the genes of the methylenetetrahydro folate reductase (MTHFR), fibroblasts growing factor receptor 4 (FGFR4) and hemochromatosis (HFE) were also investigated, searching for new possible molecular markers for prognosis or diagnosis in breast cancer. Prognosis variables as age, triple negative tumors, lymph nodes status, HER2, p53, Ki67, tumor size and grade were investigated and related to the presence or absence of metastasis/death, and to both plasma levels of D dimmer and tissue factor. The data taken together allow to infer that the hemostatic system is activated in patients with breast cancer at the diagnosis, which is indicated by levels of D dimmer and tissue factor significantly more elevated compared to the those for the control group. This fact confirms previous reports on a hypercoagulability state in patients with malignant diseases. However, the levels of D dimmer failed as a prognosis marker at the diagnosis. By other hand, they correlated with the severity of the disease assessed by presence of metastasis/death. The assessment of this marker did not allow infer about disease-free survival. Prognosis variables did not show to be associated to either development of metastasis/death or with the plasma levels of D dimmer or tissue factor. H63D mutation in homozygosis in the gene HFE showed to be associated with breast cancer, while the C677T mutation in the gene MTHFR showed to be associated with metastasis/death, lymph nodes involvement and superexpression of both HER2 and Ki67. The Gly388Arg in the gene FGFR4 polymorphism showed to be associated to Ki67 and to a higher probability for developing metastasis/death as compared to the other genetic alterations. The promising results for D dimmer as a disease progressing marker, as well as the preliminary results of molecular analyses, address to new studies involving a continuous measurement of this hemostatic marker and molecular profiling techniques in a larger number of women with hormone negative receptor breast cancer.